2018
DOI: 10.1021/acssuschemeng.7b04636
|View full text |Cite
|
Sign up to set email alerts
|

Etherification Reactions of Furfuryl Alcohol in the Presence of Orthoesters and Ketals: Application to the Synthesis of Furfuryl Ether Biofuels

Abstract: Changes made as a result of publishing processes such as copy-editing, formatting and page numbers may not be reflected in this version. For the definitive version of this publication, please refer to the published source. You are advised to consult the publisher's version if you wish to cite this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…It must be mentioned that the low temperature applied improved selectivity by decreasing the production of hydrolysis products, and the competing polymerization reactions resulting in humin by-products. 158 In 2015, Zhang et al utilized ZrO 2 supported Pd(OH) 2 (Pd(OH) 2 /ZrO 2 ) as a new catalytic system for the synthesis of aryl ethers (137) via the reaction of substituted cyclohexanones (136) with orthoesters (4, 5, 127) as both dehydrating and nucleophilic reagents under an atmospheric pressure of oxygen (0.5 MPa) at 140 C for 6 h (Scheme 36). It was found that in the presence of TMOF (4) reagent, the corresponding aryl ethers were obtained in moderate to good yields.…”
Section: Etherication and Esterication Reaction And Johnson-claisementioning
confidence: 99%
See 1 more Smart Citation
“…It must be mentioned that the low temperature applied improved selectivity by decreasing the production of hydrolysis products, and the competing polymerization reactions resulting in humin by-products. 158 In 2015, Zhang et al utilized ZrO 2 supported Pd(OH) 2 (Pd(OH) 2 /ZrO 2 ) as a new catalytic system for the synthesis of aryl ethers (137) via the reaction of substituted cyclohexanones (136) with orthoesters (4, 5, 127) as both dehydrating and nucleophilic reagents under an atmospheric pressure of oxygen (0.5 MPa) at 140 C for 6 h (Scheme 36). It was found that in the presence of TMOF (4) reagent, the corresponding aryl ethers were obtained in moderate to good yields.…”
Section: Etherication and Esterication Reaction And Johnson-claisementioning
confidence: 99%
“…166 The cross-coupling reaction of aryl iodides (155) with 3,3,3triethoxy-1-propyne (156) using dichlorobis(triphenylphosphine) palladium [(PPh 3 ) 2 PdCl 2 ] and cuprous iodide (CuI) in triethylamine (Et 3 N) at room temperature led to the production of 3,3,3-triethoxy-1-aryl-1-propyne within 1-4 h, which aer isolation was subsequently reacted with a catalytic amount of p-TSA in benzene at room temperature for 12 h to yield the ethyl arylpropiolates (157) (Scheme 42). 167 Padmapriya and co-workers reported the alkylation of sulfonic acids (158) (163,164) and triic acid (TfOH) at À20 to 40 C, yielding the corresponding alkyl 2-(naphthalen-1-yl)propanoate (165) (Scheme 45). In this reaction the effect of different parameters, such as the type of catalyst, catalytic amounts of Lewis acid, the nature of the orthoester, and temperature were investigated.…”
Section: Etherication and Esterication Reaction And Johnson-claisementioning
confidence: 99%
“…Recently Chaffey et al . reacted furfuryl alcohols with TMOF and TEOF in the presence of catalytic amounts of zeolite secondary mobil–5 ZSM‐5 (Si/Al ratio=30 : 1, ZSM‐5‐(30)) in short alcohols or dimethyl carbonate DMC (as a substitute for traditional solvents).…”
Section: Carbon‐carbon and Carbon‐heteroatom Bond Formation Reactionsmentioning
confidence: 99%
“…The unraveled potential of the interaction of orthoester with alcohols in the presence of various solid acids, has been very recently exploited for the preparation of furanic ethers [64].…”
Section: Direct Etherification Of Hmf and Furfuralmentioning
confidence: 99%